25. HEALTH INSURANCE CO-PAYMENT POLICIES FOR RARE DISEASES: INTERNATIONAL LESSONS LEARNED (Vietnam Journal of Community Medicine, 2026)
Objective: The high cost of treatment, prolonged diagnostic delays, and limited access to medications had made rare diseases a significant challenge for health insurance systems. In the context of Vietnam’s proposed amendment to the Law on Health Insurance—which included full coverage and the removal of referral requirements for patients with rare diseases—this study was conducted to synthesize international experiences regarding co-payment levels and healthcare access mechanisms for this patient group.Methods: A literature review was carried out using academic databases and international policy reports, focusing on health insurance reimbursement and referral management in the context of rare disease treatment.Results: Policy analysis from eight countries and the European Union revealed three major models: (1) full exemption from co-payment for patients with rare diseases (e.g., the UK, Italy, Australia, Taiwan); (2) conditional exemptions such as income-based cost caps, HTA waivers for orphan drugs, or classification of rare diseases under long-term conditions with enhanced coverage (e.g., Japan, Germany, France); and (3) the enactment of rare disease-specific laws or national strategies, providing legal and financial foundations for long-term support. Several countries also implemented dedicated support funds—such as LSDP (Australia), IMF (UK), and AIFA 5% (Italy)—to ensure access to treatment.Conclusion: International experiences suggested that adapting co-payment and referral policies in a flexible, patient-centered manner aligned well with the specific nature of rare diseases. The proposed reforms in Vietnam’s amended Health Insurance Law—such as eliminating referrals and offering full reimbursement—represented a sound policy direction, but required technical regulations, cost data, and a clear patient classification system to be effectively implemented.
Keywords: Rare diseases; Health insurance; Co-payment; Referral system; Orphan drugs.